(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study aims at examining the usage of technology in HR practices in hotel industry. Technology is a tool that has and is still being globally used for the benefit of humanity. It is being utilized by various hotel industries to meet the need soffits various stakeholders. On are gular basis, new and upgraded versions of technology are being invented. It has been observed that, the distinguishing factor between organizations is their ability to use modern technology to deliver HR service. Technology in HR practice can be used to improve an organizations performance. In as much as technology has been of immense benefit to organizations, it also comes with its challenges and other downsides. This study provides an outlay of how HR technology emerged and its gradual acceptance and practice in hotel industry. The research isintendedtoshowtheneedtounderstandtheuseoftechnologyinHRpracticesinhotelindustrya ndthe need to curbits challenges.